TRAINING OF EDUCATORS FROM THE PERSPECTIVE OF INCLUSIVE EDUCATION IN NON-FORMAL CONTEXTS - Vasconcellos, Talita Silva Perussi; Carneiro, Relma Urel Carbone (Seven Editora, 2025)
Understanding that the inclusion of the Special Target Public Student (PAEE) must take place in all teaching environments, this work brings the inclusive reality in non-formal teaching organizations. The general objective of the study was: To analyze the impact of a proposal for continuing education regarding the process of inclusion of the PAEE student in a non-formal organization and as specific objectives: 1. To know how inclusion in a non-formal organization takes place 2 Design and develop a collaborative proposal for training on inclusion, based on current educational practices. 3. Evaluate the training proposal and its impacts. The research was carried out with a qualitative approach and was characterized as collaborative research. 19 participants from different non-formal education organizations participated, first answering a questionnaire characterizing and surveying training demands, later, in face-to-face meetings, a training program for educators was carried out. At the end of the meetings and after six months of the end of the training, evaluation instruments were applied, which aimed to know the impacts of the training in question. As a result, it was observed that the study that was developed contributed to the related areas of knowledge, encouraging greater discussions about the training of educators in non-formal teaching organizations. DOI: https://doi.org/10.56238/sevened2025.038-029